Early spring orchard pollinators spill over from resource‐rich adjacent forest patches. Issue 3 (6th January 2023) - Urban‐Mead, Katherine R.; Van Dyke, Maria; Muñiz, Paige; Young, Andrew D.; Danforth, Bryan N.; McArt, Scott H.
Abstract: Pollinator communities are more abundant and diverse in agricultural matrices with more natural habitat, although the reasons for these correlations remain unclear. It is possible that forest fragments and edges provide resources for pollinators in important early weeks of spring, after which time those insects can then 'spill over' into crops such as apple orchards during bloom. To explore how forest edges may feed and therefore promote flower visitor communities in adjacent agricultural habitats, we sampled springtime pollinators in nine orchards and their adjacent forest edge canopies and understories. We identified pollen consumed by pan‐trapped bees and flower flies to assess if pollinators ate pollen where they were caught, and if their diets similarly 'spill over' from forest to orchard. We further explored sex differences in habitat usage. Our spatially replicated sampling found that bee and flower fly abundance peaks first in the forest understorey, then in the forest canopy and finally in the orchard. Analysis of digestive tracts showed significant usage of forest canopy pollen throughout the spring, especially before apple bloom. Pollinators had often eaten pollen from a different habitat than the one in which they were caught, suggesting frequent movement between habitats. Digestive tract pollen is an underused but powerful avenue for ecological insight. In Andrena, which are important orchard pollinators and one of the most abundant wild bee taxa in this study, male bees were primarily found in the woods but not the orchards where conspecific females were later active. Synthesis and applications : Forested areas, especially forest canopy trees, provide large amounts of early spring resources that facilitate build‐up and spillover of wild pollinator populations into apple orchards during bloom. Forests also provide critical habitat for male bees, which were rarely found in orchards. Despite their importance for bee reproduction, the needs of male bees are usually not considered in conservation planning. Overall, our data indicate that ensuring there is adequate forest habitat adjacent to orchards can improve the long‐term sustainability of pollinator populations that provide essential crop pollination services. Abstract : Forested areas, especially forest canopy trees, provide large amounts of early spring resources that facilitate build‐up and spillover of wild pollinator populations into apple orchards during bloom. Forests also provide critical habitat for male bees, which were rarely found in orchards. Despite their importance for bee reproduction, the needs of male bees are usually not considered in conservation planning. Overall, our data indicate that ensuring there is adequate forest habitat adjacent to orchards can improve the long‐term sustainability of pollinator populations that provide essential crop pollination services. Resumen: Las comunidades de polinizadores son más abundantes y diversas en matrices agrícolas con más hábitat natural, aunque las razones de estas correlaciones no están claras. Es posible que los fragmentos y los bordes del bosque proporcionen recursos para los polinizadores en las primeras semanas importantes de la primavera, después de lo cual esos insectos pueden "spill over" en cultivos como los huertos de manzanos durante la floración. Para explorar cómo los bordes del bosque pueden alimentar y, por lo tanto, promover las comunidades de visitantes de flores en hábitats agrícolas adyacentes, tomamos muestras de polinizadores primaverales en nueve huertos y los sotobosques y doseles de los bosques adyacentes. Identificamos el polen consumido por las abejas y las moscas de la familia Syrphidae atrapadas para evaluar si los polinizadores comieron el polen donde fueron atrapados y si sus dietas se "spill over" de manera similar del bosque al huerto. Exploramos más a fondo las diferencias sexuales en el uso del hábitat. Nuestro muestreo replicado espacialmente encontró que la abundancia de abejas y moscas de la familia Syrphidae alcanza su punto máximo primero en el sotobosque, luego en el dosel del bosque y finalmente en el huerto. El análisis de los tractos digestivos mostró uso significativo del polen del dosel del bosque durante la primavera, especialmente antes de la floración de los manzanos. Los polinizadores frecuentemente habían comido polen de un hábitat diferente al que los atraparon, lo que sugiere un movimiento frecuente entre hábitats. El polen del tracto digestivo es una vía infrautilizada pero poderosa para el conocimiento ecológico. Con respecto a Andrena, que son importantes polinizadores de huertos y uno de los taxones de abejas silvestres más abundantes en esta investigación, las abejas macho se encontraron principalmente en los bosques, pero no en los huertos donde las hembras conespecíficas estuvieron activas más tarde. Síntesis e implicaciones: Las áreas boscosas, especialmente los árboles del dosel del bosque, proporcionan grandes cantidades de recursos a principios de la primavera que facilitan la acumulación y el "spill over" de poblaciones de polinizadores silvestres en los huertos de manzanos durante la floración. Los bosques también proporcionan un hábitat crítico para las abejas machos, que rara vez se encuentran en los huertos. A pesar de su importancia para la reproducción de las abejas, las necesidades de las abejas machos generalmente no se consideran en la planificación de la conservación. En general, nuestros datos indican que garantizar que haya un hábitat forestal adecuado junto a los huertos puede mejorar la sostenibilidad a largo plazo de las poblaciones de polinizadores que brindan servicios esenciales de polinización de cultivos.